2008
DOI: 10.1186/1471-2164-9-439
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gene regulatory modules of heat shock response in yeast

Abstract: Background: A gene regulatory module (GRM) is a set of genes that is regulated by the same set of transcription factors (TFs). By organizing the genome into GRMs, a living cell can coordinate the activities of many genes in response to various internal and external stimuli. Therefore, identifying GRMs is helpful for understanding gene regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…4). Interestingly, Cst6 belongs to five novel heat-responsive TFs recently identified using a gene regulatory module which was constructed based on TF-promoter binding matrix and heat shock gene expression data (63). In addition, Cst6 is reported to regulate genes involved in the cell cycle and DNA processing (63).…”
Section: Differential Proteomic Patterns Of Industrial Strains In Tr mentioning
confidence: 99%
See 1 more Smart Citation
“…4). Interestingly, Cst6 belongs to five novel heat-responsive TFs recently identified using a gene regulatory module which was constructed based on TF-promoter binding matrix and heat shock gene expression data (63). In addition, Cst6 is reported to regulate genes involved in the cell cycle and DNA processing (63).…”
Section: Differential Proteomic Patterns Of Industrial Strains In Tr mentioning
confidence: 99%
“…Interestingly, Cst6 belongs to five novel heat-responsive TFs recently identified using a gene regulatory module which was constructed based on TF-promoter binding matrix and heat shock gene expression data (63). In addition, Cst6 is reported to regulate genes involved in the cell cycle and DNA processing (63). Therefore, much more significant correlation of Cst6 to the proteomic variation observed in TR than in HSR implied a potential crosstalk between cell cycle modulation and thermotolerant adaptation.…”
Section: Differential Proteomic Patterns Of Industrial Strains In Tr mentioning
confidence: 99%
“…As expected, most of the analyses have shown that heat shock proteins are very important for the thermotolerance, but in addition, several proteins involved in oxidative stress response, signal transduction, transcription, translation, and carbohydrate or nitrogen metabolism were observed (1,19,40). In S. cerevisiae, the heat shock response is mostly controlled by Hsf1, Msn2/Msn4, and Hac1, and targets for these transcription factors have already been identified (22,27,(63)(64)(65)(66). Upon heat shock, the A. fumigatus Hsf1 homologue has increased transcription (1,22).…”
Section: Discussionmentioning
confidence: 59%
“…In this regard, a TF is considered as a cell cycle TF if a statistically significant portion of its regulatory targets is the cell cycle-regulated genes (identified by Spellman et al (1998)). The hypergeometric distribution is used to test the statistical significance (Wu and Li, 2008a). The procedure for determining whether TFj is a cell cycle TF is as follows.…”
Section: Identification Of Cell Cycle Tfsmentioning
confidence: 99%